Sistem Informasi Pencarian Bahan Baku Tambak Udang Menggunakan Algoritma Haversine Berbasis Android Studi Kasus Lhokseumawe - Angga Pratama; Desvina Yulisda; Rafika Rafika (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The pond is one of the livelihoods of the Indonesian people. The pond is used as a means of aquaculture. Farmed animals are aquatic animals such as fish and shrimp. One of the aquaculture commodities that are in great demand by pond owners is van name shrimp (Litopenaeus Vannamei). Before starting a shrimp farm, the farm owner must find the raw materials needed for the shrimp pond. In the search for raw materials for shrimp ponds, the owners of the ponds have to go directly to the point of sale of raw materials for shrimp ponds in the Lhokseumawe area. To find raw materials for this shrimp pond, people certainly need technology that can make it easier to find the desired needs. By utilizing advances in mobile technology, this study aims to build an Android-based Information System for Searching for Raw Materials for Shrimp Ponds in Lhokseumawe Area. This information system can also manage and display information about shrimp ponds.